(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This study takes into account the newly developed hybrid ARIMA-FIGARCH. We use the daily price index of the S&P 500. The data employed for this study was secondary in nature for all the variables and was obtained from the publications of the Central Bank of Nigeria Bulletin, the National Bureau of Statistics, and the World Bank Statistics Database, dated January 2005 to December 2020. Also, the result of the Jarque-Bera test indicated that the p-values for all variables were less than the alpha level of significance (0.05). Hence, we would reject the null hypothesis that the data for all variables are normally distributed. Also, unit root tests were conducted using ADF and KPSS tests. The result of the ADF test shows that the variable is stationary at a level of 5% significance. That means the variables are integrated in order zero, i.e., 1 (0). And for the KPSS test, 0.881749 is greater than 0.463000, indicating that it is not significant at level 1, indicating that it is not stationary, whereas KPSS is 0.011158, which is less than 0.463000, indicating that it is stationary at level 1. The unit root test is necessary in order to determine the nature of the series and to avoid getting spurious results. We estimate the fractional difference order, d, by the Geweke and Porte-Hudak (GPH) method for testing the present and long memory of the series. The results show that the value...